Avaliação microestrutural e mecânica de chapas de TI-16NB obtidas por tape casting - Santos, Diego Michael Cornelius dos (2022)
Titanium and its alloys allow a wide range of applications as they have a distinct combination of characteristics, such as low density, high mechanical strength and excellent corrosion resistance. In addition, they also allow the combination of different phases and microstructures, which can be obtained as a function of the addition of alloying elements and through different processing parameters. In this context, the aim of this work has been the microstructural and mechanical evaluation of the Ti-16Nb alloy obtained by tape casting, having as object of comparison the different sintering temperatures and size of the niobium particles. The work was carried out through the development of five steps: i) preparation of powders and organic binders, which involves the separation and mixing of materials; ii) molding and cutting of samples; iii) sintering according to heating and cooling rates, temperatures and exposure time; iv) metallographic preparation, performed by grinding and polishing the samples v) metallographic and mechanical characterization, which involves optical and electronic microscopy tests, energy dispersive spectroscopy, X-ray diffractometry and Vickers hardness test. Regarding the evaluation of the samples, the results show that the sintering temperature is an important parameter, because at higher temperatures the samples showed greater changes in the microstructure and in the phases present in the alloy. The size of the niobium particle also influenced the study, and the samples with smaller particles were the ones that showed greater hardness and less porosity. In general, the porosity of the samples was between 30.8% and 14.1% and it decreased as the sintering temperature increased, contrary to what occurred with the hardness, which increased as the samples were sintered at higher temperatures. Microscopic evaluation showed few microstructural changes in samples sintered at 900 °C and 1000 °C, while at temperatures of 1100 °C and 1200 °C there was greater densification of the alloy and an increase in the  phase content of titanium in the samples. The mapping of the elements carried out in the energy dispersive spectroscopy test allowed us to determine that the  phase of titanium is rich in niobium, with this diffusion occurring more significantly at 1200 °C. X-ray diffraction highlighted the influence of temperature and particle size on the emergence of the  phase. Finally, Vickers hardness tests show that samples sintered at higher temperatures and with smaller grains have higher hardness values.